Modeling human retinal ganglion cell axonal outgrowth, development, and pathology using pluripotent stem cell–based microfluidic platforms - Cátia Gomes; Kang-Chieh Huang; Sailee S. Lavekar; Jade Harkin; Carson G. Prosser; Yue Fang; Claire Kalem; Adrian Oblak; Chi Zhang; Jason S. Meyer (Proceedings of the National Academy of Sciences, 2025)
Retinal ganglion cells (RGCs) are highly compartmentalized neurons whose long axons serve as the sole connection between the eye and the brain. In both injury and disease, RGC degeneration occurs in a similarly compartmentalized manner, with distinct molecular and cellular responses in the axonal and somatodendritic regions. The goal of this study was to establish a microfluidic-based platform to investigate RGC compartmentalization in both health and disease states. Human pluripotent stem cell (hPSC)-derived RGCs were seeded into microfluidic devices that allow physical separation of axons from the somatodendritic compartment, enabling precise study of each region. Initial experiments characterized axonal outgrowth and the specific segregation of axons and dendrites. We then examined compartment-specific phenotypes in RGCs carrying the OPTN(E50K) glaucoma mutation compared to isogenic controls, including differences in axonal growth and axonal transport efficiency, with OPTN-mutant RGCs showing reduced axon length and slower transport, hallmarks of neurodegeneration. Axonal RNA-seq analyses revealed transcriptomic alterations related to disease states, including specific transcriptomic changes along OPTN axons. To assess glial influences on axonal health, we developed models with astrocytes localized specifically to the proximal axonal compartment and modulated their disease states to simulate pathological conditions. Importantly, the induction of diseased astrocytes solely along proximal axons triggered compartment-specific neurodegenerative changes in RGCs. Collectively, this platform represents a successful recapitulation of the spatially distinct features of hPSC-derived RGCs under both healthy and disease conditions, offering a physiologically relevant, human-specific in vitro system to study neuronal development, axon–glia interactions, and mechanisms underlying neurodegeneration.